Penerapan Fermentasi Biji Kakao (Theobroma cacao L.) di Kabupaten Pidie Jaya, Aceh - Juanda Juanda; Sri Hartuti; Mujiburrahmad Mujiburrahmad (Warta Pengabdian Andalas, 2023)
Cocoa is one of the primary commodities in Meureudu and Trienggadeng Sub-districts, Pidie Jaya Regency. Many cocoa farmers in the sub-districts still need to understand the process and benefits of fermenting cocoa beans. Bean fermentation is essential because it can increase biochemical changes and the concentration of flavour precursors in cocoa beans so that it has a high selling value. This community service activity was implemented using counselling methods, demonstrations, and the submission of fermenters. It was held for two days assisting and attended by 59 of 70 farmers from two groups. Results showed the participants' positive response to the partaking activities and their interest in fermenting cocoa. Through the activities that have been carried out, cocoa farmers understand and can maintain a good cocoa bean fermentation process. Assistance to farmer groups must be continuously conducted so that cocoa farmers remain consistent in fermenting cocoa beans to produce better quality cocoa.